Neighborhood Social Environment and Patterns of Depressive Symptoms among Patients with Type 2 Diabetes Mellitus - O’Donnell, Alison (Community Ment Health J, 2015)
This study sought to examine whether neighborhood social environment was related to patterns of depressive symptoms among primary care patients with type 2 diabetes mellitus (DM). Neighborhood social environment was assessed in 179 patients with type 2 DM. Individual patient residential data at baseline was geo-coded at the tract level and was merged with measures of neighborhood social environment. Depressive symptoms at baseline and at 12-week follow up were assessed using the nine-item Patient Health Questionnaire (PHQ-9). Patients in neighborhoods with high social affluence, high residential stability, and high neighborhood advantage were much less likely to have a persistent pattern of depressive symptoms compared to a pattern of few or no depressive symptoms (adjusted odds ratio (OR) = 0.06, 95% confidence interval (CI) [0.01, 0.36]). Detrimental neighborhood influences may amplify risk for persistent depressive symptoms.